"Water‐in‐Salt" Electrolytes for Supercapacitors: A Review. Issue 12 (21st May 2021) - Tian, Xue; Zhu, Qizhen; Xu, Bin
Abstract: "Water‐in‐salt" (WIS) electrolytes, which have more salt than the solvent in both mass and volume, show promising prospects for application in supercapacitors due to their wide electrochemical stability window (about 3 V), considerable ion transport, high safety, low cost, and environmental friendliness. This Review summarizes the advances, progress, and challenges of WIS electrolytes in supercapacitors. The working mechanisms, reason for the wide electrochemical stability window, typical systems, challenges, and modification strategies of the WIS electrolytes in supercapacitors are discussed. Moreover, the application of WIS electrolytes in symmetric and asymmetric supercapacitors are presented. Finally, perspectives and the future development direction of WIS electrolytes are given. This Review is expected to provide inspiration and guidance for designing WIS electrolytes with advanced performance and push forward the development of high‐performance aqueous supercapacitors with high cell voltage, good rate performance, and thus high energy density and power density. Abstract : Salted energy : "Water‐in‐salt" electrolytes, with wide electrochemical stability window, fast ion transport, high safety, low cost and environmental friendliness, show promising prospect for application in high‐performance aqueous supercapacitors.